If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7x + 62 = 3x + 38 Reorder the terms: 62 + 2x + -7x = 3x + 38 Combine like terms: 2x + -7x = -5x 62 + -5x = 3x + 38 Reorder the terms: 62 + -5x = 38 + 3x Solving 62 + -5x = 38 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 62 + -5x + -3x = 38 + 3x + -3x Combine like terms: -5x + -3x = -8x 62 + -8x = 38 + 3x + -3x Combine like terms: 3x + -3x = 0 62 + -8x = 38 + 0 62 + -8x = 38 Add '-62' to each side of the equation. 62 + -62 + -8x = 38 + -62 Combine like terms: 62 + -62 = 0 0 + -8x = 38 + -62 -8x = 38 + -62 Combine like terms: 38 + -62 = -24 -8x = -24 Divide each side by '-8'. x = 3 Simplifying x = 3
| P=2(pi)r+2x | | 7x-7y=49whatisx | | 8x+9x-3x=52+4 | | (3x-2)/5=(2x-1)/4 | | 2x/3+y/5=0 | | c-8=-17 | | -9d=36 | | 2(x+5)=9x+2-7x+8 | | -(x-6)-6x=-8x+3(-x-6) | | 9x+3=2x+52 | | A+2b/4+4a | | 5(x+4)=2x+29 | | 2q^2+75/2=-20q | | x^4+x=1 | | -8+t=-6 | | X^2=3X-4 | | 4x^5/6x^-3 | | -4(k-1)=10-6k | | 4x^5/6x-3 | | 0=-10x^2+3500x-66000 | | 2d^2+4d-13=0 | | 3=11+4n | | 4x(-2)=12 | | log(6)(x)-log(6)(x+1)=2 | | 14x+3=0 | | y-0.2=0.6(y+3) | | (7x^2+5x/x^2+1)-(5x/x^2-6)=0 | | 1.4=0.3x+1/2*4x^2 | | 2=7+5a | | 7x+14=8x-10 | | -(w+0.2)=0.6(y+3) | | 2.25=a/740 |